THE EFFECTIVENESS OF ROLE PLAY STRATEGY IN TEACHING SPEAKING (The Case of English department students of Majalengka University) - Nurhidayah, Yayah (Jurnal Educatio, 2016)
The success of learning is much influenced by the extent to which the students are involved in teaching and learning process. Many students fail to reach the goal of the English teaching. They are not able to communicate with the language either orally or in written form although they have learned English for many years. It call to the lecturer to find the appropriate teaching strategy. The field of this research is teaching speaking. Furthermore, this research focuses only on the observing and analyzing data about applying Role - Play strategy in the speaking class; to find out the effectiveness of Role - Play strategy and to find out students response toward applying this strategy. This research uses Classroom Action Research (CAR). The Classroom Action Research consists of four phases those are: Planning, Acting, Observing, and Reflecting. The subject of this research is PBI I - A students of English Department. In collecting the data, this research uses observation, questionnaire, and test. Based on the research findings, it can be said that using role play strategy is success since the criteria of success were achieved. The criterion of action success is 75% of students could achieve the target score. It can be concluded that Role - Play strategy is effective and students response toward applying this strategy are good and enthusiasts.Â Keywords: Role Play, Speaking and Teaching speaking